Effects of supplemental betaine to semen extenders on semen quality in boars - Lugar, D W (Transl Anim Sci, 2018)
Two experiments were conducted to evaluate the use of supplemental betaine in commercially available semen extenders. In experiment 1 (Exp1), semen was collected from six mature boars once weekly for 6 wk (3 wk in summer and 3 wk in winter) and diluted into a commercial extender with the following betaine concentrations: 0, 51, 102, and 205 mM. Semen samples were analyzed on the day of collection (D0) and after 72 h of storage (D3). In experiment 2 (Exp2), semen was collected from four mature boars for 3 wk and was diluted into three commercially available semen extenders (short term, ST; long term with bovine serum albumin, BSA; and long term without BSA, LT), with and without supplemental betaine (0 and 70 mM), and analyzed on D0 and D3. Semen was analyzed using computer-assisted sperm assessment (Ceros II, IMV) and morphology using phase contrast microscopy. In Exp1, total motility on D0 was less for 0 mM than that for 102 mM (P = 0.038) and was substantially reduced for 205 mM compared with 102 mM (P < 0.001). Supplementation with 205 mM betaine resulted in a significant reduction in the percentage of morphologically normal sperm (P < 0.001). In Exp2, 70 mM betaine reduced the total motility compared with 0 mM (P = 0.010) but did not impact percentage of normal sperm (P = 0.942). The use of supplemental betaine may partially alleviate the dilution effect on sperm, though boar genetics may impact its efficacy. Further research is needed to make a definitive conclusion.